A retrospective study of hepatitis B vaccination in preterm birth and low birth weight infants born to hepatitis B surface antigen-positive mothers: Time to close the policy-practice gap. Issue 7 (30th December 2022) - Qin, Wei; Wang, Yao; Zhang, Xiaqing; Pan, Fan; Cheng, Kai; Sui, Haitian; Xie, Shaoyu
ABSTRACT: National Immunization Program-version 2016 (ISIV-NIP-v2016) recommended a 4-dose hepatitis B vaccine (HepB) schedule for preterm birth (PTB) and low birth weight (LBW) infants born to HBsAg-positive mothers. However, the implementation of this immunization strategy in the past five years has not been fully evaluated in China. We reviewed the data of pregnant women and live-born infants from 24 hospitals between 2016 and 2021 in Lu'an, Anhui province, to estimate the prevalence of PTB, LBW, and hepatitis B virus (HBV) infected pregnant women. We analyzed the vaccination status of HepB and HBIG among PTB and LBW infants born to HBsAg-positive mothers. A total of 160 222 pregnant women and 159 613 live-born infants were included in this study. The estimated prevalence of PTB, LBW and HBV-infected pregnant women was 3.86% (range: 3.28%-5.10%), 2.77% (range: 2.12%-3.66%), and 3.27% (range: 3.03%-3.49%), respectively. We screened 340 PTB and LBW infants born to HBsAg-positive mothers between 2016 and 2020. We found that the coverage of HepB and HBIG among them was 100% and 99.39%. However, the timely vaccination rate of the HepB birth dose was only 78.59% and only four children (1.22%) received the 4-dose HepB as recommended by ISIV-NIP-v2016. The 4-dose of HepB for PTB and LBW infants born to HBsAg-positive mothers recommended by ISIV-NIP-v2016 was not fully implemented. A strong public health intervention should be taken to close the policy-practice gap in China in the future.